The Environmental Protection Agency presents an award to Tufts for the Tufts Climate Initiative. Photo 146 - Ko, Melody (Tufts Archival Research Center, 2008)
The Environmental Protection Agency presents an award to Tufts for the Tufts Climate Initiative. President Lawrence Bacow and others speak in the Lincoln Filene room.